CENSUS OF POPULATION 1980 - Chapman, Bruce (dirección) (1980)
CONTENIDO: T. 1 V. 1 CHARACTERISTICS OF THE POPULATION: CHAPTER C. GENERAL SOCIAL AND ECONOMIC CHARACTERISTICS PART 1UNITED STATES SUMMARY. -- T. 1. V. 1 CHAPTER B GENERAL POPULATION CHARACTERISTICS